La inteligencia emocional y sus efectos en el comportamiento disruptivo, en los niños de los sextos años de Educación Básica de la Unidad Educativa La Maná en el periodo lectivo 2016 - 2017 - Galeas Armijo, Walter Xavier (2017)
The IQ predicts only 10 to 20 percent of success in life; the remaining eighty percent depends on other types of variables, such as social class and to a large extent, emotional intelligence. Controlling impulses, deferring gratification, regulating one's moods, anguish, and trusting one another, seem to be far more determinant factors in achieving a fuller life than cognitive performance. The school and specifically the classroom provide a space for interaction for the teaching processes and the modeling of actions that are developed in society in general, defining the school climate as the set of activities and processes of the educational environment that determine the training of students. Emotional intelligence and its effects on disruptive behavior in the six-year-old boys and girls of “La Maná” Educational Unit made it possible to verify cases of children and adolescents who have been the cause of constant problems for the teacher, resulting in a loss of time in the teaching process. Educating emotional intelligence was achieved through the use of a methodological guide reducing the disruptive behavior of students through the use of a methodological guide. In this way, the education of emotional intelligence within a formative process will reduce the disruptive behavior of children. The methodology such as field research, descriptive, qualitative methodology and methodological guidance allowed a good management of emotions with the reduction of disruptive behaviors in boys and girls.